Engaging with customer experience while visiting a shopping centre - Pinto, Rita Maria Lopes (2022)
This project aims to assess the perception of Centro Colombo customers regarding the different experiences promoted by this shopping centre. With a deeper knowledge about customers preferences, Sonae Sierra managers hope to channel their efforts on experiential strategy for attaining satisfied customers. The project entails an extensive literature review, along with external, internal and competitive analyses. This reviews and analyses were the foundations for the creation of this project’ survey. By examining customer’s responses to this survey, it was possible to identify the dimensions of customer experience which are the most esteemed by consumers and which should be improved. In addition, a statistical analysis was performed, and confirmed the existing relationship between a customer encounter with a positive experience in the shopping centre and consumers feeling engaged towards it. This project includes an improvement proposal gathering new experiences that seem promising both for customers and Centro Colombo’s managers.